Surveying The Standard of Outpatient Visit Time among General Hospitals: A case study in Qazvin - edris hasanpoor; bahram delgoshie; Hassan Gorji; Masoomeh khogam; Mobin Sokhanvar (Tehran University of Medical Sciences, 2015)
Background: one of the most essential components in patient- physician relationship is the length of visit. Short time visit can affect visit quality and patient- physician relationship. This study aimed at comparing specialists visit length with standards in general hospitals of Qazvin. Materials and Methods: This cross-sectional study conducted in general hospitals of Qazvin  in 2013. 428 patients were randomly selected to participate who were referred to the outpatient clinics of selected general hospitals. Studied specialties were including Internal Medicine, Surgery, Pediatrics and Obstetrics and Gynecology. In order to data collection, a Checklist including physician and patient related items was used and data analysis performed using SPSS version 19. Results: The study results revealed the mean score of outpatientschr('39') visits length was 4.67±2.43 minutes which had a significant difference from standards (p<0.0001).Higher mean score was relate to  pediatrics (2.55±7.08) and the lower one was internal physicians (1.82±3.93). Conclusion: In this study, Visit time in developed countries was lower than developing ones. Several factors were identified which affect visit time. Thus, decision makers should use the results to improve outpatients visit quality.